Application of PAN/α-Fe2O3-Bentonite as A Photocatalytic Membrane for The Photodegradation of Methylene Blue - Sitompul, Dina Wardani; Kemala, Tetty; Darmawan, Noviyan (Jurnal Kimia Valensi, 2023)
The intricate molecular structure of the dyes in wastewater makes it difficult to biodegrade, which could harm the environment. Currently, semiconductor-based photocatalytic methods are being developed to remove dyes from water. In this study, the α-Fe2O3-bentonite photocatalyst was synthesized by mechanical milling and immobilized in polyacrylonitrile (PAN) membrane by phase inversion. Analysis of the composition and surface morphology of the synthesized samples was carried out by FTIR, XRD, and EDX. The performance of the photocatalytic membrane was studied by investigating the removal of methylene blue (MB). Photocatalytic membrane with 2% α-Fe2O3-bentonite had the best performance in removing MB (10 ppm) that reached 99.84% at pH 11.5 with an irradiation time of 300 minutes under direct sunlight. The reuse cycle of the photocatalytic membrane was also carried out and the results showed that there is no significant change in the photodegradation efficiency after 3 cycles. Photocatalyst immobilization on PAN membranes is proven to overcome the post-recovery problem of photocatalysts and making easier to reuse. The photocatalyst membrane synthesized in this study can be used as an alternative for removing dyes from water.